The Indians and the Constitution of 1812 - Hünefeldt, Christine (1978)
Little is known about the results and consequences of the implementation of the Spanish Constitution of 1812 in Peru. Until now, this period has only been analyzed through the lens of the delegates and the rather rhetorical proposals presented in Cádiz; at most, secondarily when the Cusco and Huánuco uprisings have been described or only within the documentation that reviews the entire pre-emancipation period.